Water quality of the Dniester river right tributaries depending on the pollution sources - Sandu, Maria; Tariță, Anatol; Moșanu, Elena; Lozan, Raisa (Acta et Commentationes Exact and Natural Sciences, 2023)
According to the water quality Index calculated in different sections of the Dniester River tributaries the water was from medium pollution to polluted state, in Botna river (Causeni town) in 1995 and 2004 being very polluted. The water in Raut river in 2015 was of average pollution, at Balti town being polluted. A detailed study was carried out for the water from Bac river, Chisinau municipality, in 2009, through the calculated ICAcc, it was demonstrated that the water entering the territory of Chisinau municipality was already polluted, reaching very polluted downstream of the sewage treatment plant from the municipality